Climate Change: A Shadow over Nepal’s Himalayas - Manandhar, Bhai Raja (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not Available. HYDRO Nepal Journal Journal of Water Energy and Environment Issue: 17, July 2015